Strategic Human Resource: The Key to Future Business Sustainability - Asmawan, Yudhi Ferdi Andri; Rafica, Vivia Maya (Journal of Economics and Social Sciences (JESS), 2025)
This study examines the crucial role of Strategic Human Resource Management (HRM) as a key to future business sustainability. In a business landscape that continues to experience disruption, this study uses a descriptive-qualitative approach with a literature review method. The results show that Strategic HRM plays a fundamental role in creating sustainable competitive advantage. Strategic HRM transforms human resources into unique, non-imitable strategic assets and becomes a key source of innovation. In addition, this approach builds mutually beneficial relationships with employees, which encourages loyalty and high productivity. Finally, Strategic HRM ensures that every HR practice, from recruitment to compensation, is aligned with the company's overall vision and strategy.